Gigantic amoebic liver abscess in pregnancy : A case report - Chiam, K .H.; Yvonne Ai, Lian Lim; Rohela, Mahmud; Romano, Ngui; Lee, Lee Low (Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2015)
Amoebic liver abscess in pregnancy is genuinely rare in its presentation. Yet, the main issue surrounding this agenda is the diagnostic challenge that it poses especially when symptomatology is vague and clues are subtle which altogether evades the diagnosis proper. We would like to dwell mainly on these issues in hopes of enlightening clinicians towards these diagnostic dilemmas. We report an extremely rare case of amoebic liver abscess occurring in the third trimester of pregnancy in a 29-year-old lady living in an interior village in Sabah. It was a combination of biochemical, radiographic and molecular investigations that ultimately led to the final diagnosis. In lieu of the high risk of mortality amongst pregnant mothers afflicted with amoebic liver abscess, the inherent need for early diagnosis requiring a high index of suspicion is vital. Elevated alkaline phosphatase alongside neutrophilia appears to be the most consistent liver parameters in guiding clinicians towards the presence of liver abscess.